Applied problems of dynamics of pipelines, conveying liquid - Limarchenko, O. S.; Limarchenko, V. O.; Majid, M.; Timokhin, A. P. (КНУБА, 2015)
Nonlinear applied problems dynamics of pipelines with flowing liquid were considered on the basis of complex approach, which includes variational statement of the problem with automatic derivation of dynamical boundary conditions, mixed Euler-Lagrange description of fluid-structure interaction, method of modal decomposition, qualitative and numerical research of system behavior.We investigate system behavior of pipeline on moving foundation, for liquid flow with velocities, which are in a vicinity of critical velocities of liquid flow or exceed them, Different variants of foundation motion includes vibrations, rotation. Investigation showed the presence of alternative equilibrium state, near which pipeline oscillations occur for certain ranges of velocities of liquid flow.
Keywords: nonlinear applied problems; dynamics of pipelines with flowing liquid; complex approach; vibration; rotation of moving foundation; alternative equilibrium state; 532.595; 621.643:532.|595